Thermal performance of indirect forced convection solar dryer and kinetics analysis of mango. (April 2018) - Wang, Wei; Li, Ming; Hassanien, Reda Hassanien Emam; Wang, Yunfeng; Yang, Luwei
Highlights: An indirect forced convection solar dryer integrated with auxiliary heating device was presented. The thermal performance of the dryer was investigated. The influence of the drying air temperature on the drying kinetics of mango was studied. Page's model is the most appropriate model for solar drying of mango. Drying kinetics of mango was determined by using Fick's diffusion model. Abstract: In this paper, an indirect forced convection solar dryer (IFCSD) with auxiliary heating device has been presented for drying mango. The dryer consists of the evacuated tube solar air collector, three phase inverter fan, auxiliary heating device, drying chamber, and automatic control system. Moreover, the influence of different drying air temperatures on the dryer performance, the drying characteristic and the drying kinetics of mango slices in this dryer have been investigated. The experimental results showed that the temperatures at four different locations of the drying chamber were varied within a narrow band. Meanwhile, the average thermal efficiency of IFCSD was between 30.9% and 33.8%, the specific moisture extraction rate (SMER) was 1.67 (kg water/kWh) with the drying temperature of 52 °C. In addition, results revealed that the Page's model was the most appropriate for describing the drying kinetics of mango slices in IFCSD. The effective moisture diffusivity ( Deff ) values of mango slices were obtained from the Fick's diffusion equation varying from 6.41 × 10 −11 to 1.18 × 10 −10 m 2 /s, over the temperature range of 40–52 °C. Furthermore, results revealed that Deff values increased with the increasing of drying air temperatures, due to the increase of heating energy would increase the activity of water molecules of mango slices. Thus, this study contributed to provide the basic theoretical and experimental data support for the follow-up research.